The Effect of Marital Relationships on the Tendency Toward Infidelity Based on Attachment Behavior in Married Women - Mohtadi, Sara; Moradi, Hojatollah; Baseri, Ahmad (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to examine the effect of marital relationships on the tendency toward infidelity based on attachment behavior in married women. Methods: This study employed a descriptive-correlational design. The statistical population consisted of all married female students at the Islamic Azad University, Central Tehran Branch, during the 2023–2024 academic year. The sampling method was multi-stage cluster random sampling, and a sample of 200 individuals was selected. Data were collected using the Attitudes Toward Infidelity Scale (ATIS) (Whatley, 2008) and the Adult Attachment Style Questionnaire by Collins and Read (1990). Data analysis was conducted using descriptive statistics (mean, median, measures of dispersion including standard deviation, skewness, and kurtosis) and correlation tests. Findings: The results indicated that attachment behavior in marital relationships predicts the tendency toward infidelity in married women. Marital relationships have a direct effect on the tendency toward infidelity based on attachment behavior. Conclusion: This study confirms that marital relationship stability influences attachment behaviors, which in turn affect the tendency toward infidelity. Secure attachment reduces infidelity risk, while avoidant and ambivalent/anxious attachment increase it, highlighting attachment’s critical role.